1991
DOI: 10.1111/j.1365-313x.1991.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression of light‐induced flavonoid synthesis by elicitor treatment of cultured parsley cells

Abstract: Summary Cultured parsley (Petroselinum crispum) cells respond differentially to UV‐containing white light and fungal elicitor. Both stimuli activate the transcription of genes encoding enzymes of partly overlapping phenylpropanoid biosynthetic pathways. Irradiation induces vacuolar accumulation of flavonoids, whereas elicitor treatment stimulates the secretion of furanocoumarins. Simultaneous treatment of parsley cells with UV light and elicitor results in quantitative changes in both responses. Irradiation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 43 publications
3
23
0
1
Order By: Relevance
“…This is particularly true for the flavonoid pathway, which has been shown to be suppressed in a number of different plant species following exposure to fungal pathogens or fungal elicitors [91-94]. Recently Schenke et al [95] demonstrated that the induction of biosynthetic pathways, in Arabidopsis, responsible for the synthesis of lignin and the phytoalexin scopoletin, by the bacterial elicitor flg22, was associated with a strong suppression of flavonol biosynthesis genes including CHS.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for the flavonoid pathway, which has been shown to be suppressed in a number of different plant species following exposure to fungal pathogens or fungal elicitors [91-94]. Recently Schenke et al [95] demonstrated that the induction of biosynthetic pathways, in Arabidopsis, responsible for the synthesis of lignin and the phytoalexin scopoletin, by the bacterial elicitor flg22, was associated with a strong suppression of flavonol biosynthesis genes including CHS.…”
Section: Discussionmentioning
confidence: 99%
“…Chalcone synthase, for example, is transcriptionally activated by UV but not by fungal elicitor . Interestingly, treatment of cultured parsley cells with fungal elicitors strongly inhibited transcription of the CHS gene and blocked its UV-B induction, whereas gene expression for the general phenylpropanoid pathway was induced (Lozoya et al 1991). Since treatment with a fungal elicitor gives rise to secretion of furanocoumarins, which are also synthesized from intermediates of the phenylpropanoid pathway, the repression of the CHS gene is almost certainly a means for abolishing the drainage of precursors for coumarin synthesis through the flavonoid biosynthetic pathway.…”
Section: Regulation Of Chalcone Synthase Gene Expression By Uv-bmentioning
confidence: 99%
“…Since treatment with a fungal elicitor gives rise to secretion of furanocoumarins, which are also synthesized from intermediates of the phenylpropanoid pathway, the repression of the CHS gene is almost certainly a means for abolishing the drainage of precursors for coumarin synthesis through the flavonoid biosynthetic pathway. By performing expression studies with different CHS promoter constructs involving the c/s-acting units, it has been shown that the same elements are involved in the down-regulation of CHS gene expression by a fungal elicitor (Lozoya et al 1991), probably by the binding of an elicitor-induced tram-acting factor which possesses a repressive function.…”
Section: Regulation Of Chalcone Synthase Gene Expression By Uv-bmentioning
confidence: 99%
“…Given the fact that elicitor treatment can also shut down the UV‐B‐induced activation of the CHS gene expression if applied hours after UV‐B onset (Lozoya et al . ), we believe that both scenarios contribute to a deacetylated H3K9 state: removal of acetyl‐groups by HDAC activity in combination with prevention of re‐acetylation by suppressing HAT recruiting TFs. These two possibilities are now included in our updated working model presented in Fig.…”
Section: Discussionmentioning
confidence: 91%